Using SWARA for the Evaluation Criteria of Connecting Airports with Railway Networks - Jure Šarić; Borna Abramović (Systems, 2025)
The optimisation of airport infrastructure capacities lacks adequate tools that would enable airport owners and managers to make strategic decisions related to sustainable development and strengthening multimodal connectivity. Assessing the sustainability of the transport system is one of the important issues in creating transport policies worldwide. In this research, the methodology of multi-criteria decision making (MCDM) was used, which can be applied to decision making and the evaluation of transport projects, considering more than one criterion in the selection process. The Stepwise Weight Assessment Ratio Analysis (SWARA) method is one of the new MCDM methods. The SWARA method will assess the weights of the selected main criteria and sub-criteria for the multimodal connection of airports to the railway transport infrastructure. In this method, the expert plays an important role in the evaluation and calculation of the criteria weights. This research also aims to respond to the need to define a framework for objective and transparent decision-making based on the assessment of the weighting factors of the selected main criteria and sub-criteria. To assess the justification for the choice of railway transport for connecting airports, financial, traffic, environmental, and availability criteria were used.